Parents’ empathic perspective taking and altruistic behavior predicts infants’ arousal to others’ emotions - Upshaw, Michaela B.; Kaiser, Cheryl R.; Sommerville, Jessica A. (Frontiers in Psychology, 2015)
Empathy emerges in children’s overt behavior around the middle of the second year of life. Younger infants, however, exhibit arousal in response to others’ emotional displays, which is considered to be a precursor to fully developed empathy. The goal of the present study was to investigate individual variability in infants’ arousal towards others’ emotional displays, as indexed by 12- and 15-month-old infants’ (n = 49) pupillary changes in response to another infant’s emotions, and to determine whether such variability is linked to parental empathy and prosociality, as indexed via self-report questionnaires. We found that increases in infants’ pupil dilation in response to others’ emotional displays were associated with aspects of parental empathy and prosociality. Specifically, infants who exhibited the greatest arousal in response to others’ emotions had parents who scored highly on empathic perspective taking and self-reported altruism. These relations may have been found because arousal towards others’ emotions shares certain characteristics with empathic and prosocial dispositions. Together, these results demonstrate the presence of early variability in a precursor to mature empathic responding in infancy, which is meaningfully linked to parents’ empathic dispositions and prosocial behaviors.